Directions of urban settlement regulation in Nakhchivan Economic District - Aliyeva, Turkana (Human Geography Journal, 2024)
The article examines the impact of the transport blockade of the Nakhchivan economic region on the socio-economic development of cities, as well as on demographic development. In addition to weak urbanization in the Nakhchivan economic region, the problem of vertical urbanization caused by harsh climatic and relief conditions has been studied in the economic-geographical aspect. For this purpose, the composition of the population employed in the economy of the economic region was studied, the current state of the manufacturing industry and its impact on urban settlement was determined. The problem of the shortage of urban economic territories is analyzed and the importance of the effective use of natural conditions and natural resources of administrative districts in regulating the settlement system is investigated, as well as the measures necessary to ensure a sustainable settlement have been analyzed. A multimodal strategy that incorporates industrialization policies, sustainable development plans, and ecological concerns is needed to solve the issues raised by urbanization. Mitigating the environmental impact of cities requires building an ecological infrastructure and promoting a harmonious interaction between urban regions and the surrounding countryside. A vital part of this effort is preserving biodiversity and developing sustainable urban environments. Putting policies in place to limit the geographic growth of cities contributes to the preservation of agricultural land, biodiversity, and ecological integrity. This calls for the creation of efficient urban expansion plans and the deployment of land use regulation instruments.